2014
DOI: 10.1515/gse-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Study and Research on Cleaning Procedures of Anaerobic Digestion Products / Studium A Výzkum Postupů Čištění Anaerobní Digesce

Abstract: This paper focuses on increasing quantities of digestate, a final product of anaerobic digestion, in biogas stations being built as alternative sources of energy. The potential use of digestate is limited due to its rather specific physical properties. This paper presents current approaches to digestate and digestate management. The objective is to compare the properties of digestate and the products of its separation via centrifuging, i.e. the liquid phase known as digestate liquor, and the solid phase referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Rehl and Müller [29] assess evaporation of the digestate in relation to a life-cycle assessment, yet there is no operational information in the text. The same relates to a study by Heviánková et al [16] who demonstrated the option to reduce the volume of LD by evaporation down to 15 percent of its original volume. Flotats et al [30] provide facts about the economy of a plant processing slurry from animal production.…”
Section: Vacuum Evaporation Of Digestate: State Of the Artsupporting
confidence: 63%
“…Rehl and Müller [29] assess evaporation of the digestate in relation to a life-cycle assessment, yet there is no operational information in the text. The same relates to a study by Heviánková et al [16] who demonstrated the option to reduce the volume of LD by evaporation down to 15 percent of its original volume. Flotats et al [30] provide facts about the economy of a plant processing slurry from animal production.…”
Section: Vacuum Evaporation Of Digestate: State Of the Artsupporting
confidence: 63%
“…Digestate is often considered as an organic fertilizer, but it contains stable organic matter, so it is rather a mineral fertilizer [8] and Babička [9] also confirmed this conclusion. The use of digestate as fertilizer is limited primarily by hygiene requirements, the presence of hazardous elements and salinity.…”
Section: Geoscience Engineeringmentioning
confidence: 90%
“…DL has a better fertilizing effect than DF due to the higher content of nitrogen (mainly mineral nitrogen) and the lower content of Fe and Al in the roots. The experimental part brought a significant finding that the organic material of DF is stable and therefore it is nearly worthless as an organic fertilizer [8].…”
Section: Growth Characteristics Of Maizementioning
confidence: 99%
“…Water flowing from such a system can be used for irrigation. Periodically, sediment is extracted from the bottom of artificial wetlands and used as organic fertilizer [12].…”
Section: Figure 1 -Methods Of Digestate Managementmentioning
confidence: 99%